Formy adresatywne jako element interkulturowy kompetencji interakcyjnej i dyskursywnej w świadomości studentów języka francuskiego - Grabowska, Monika (Neofilolog, 2019)
The present paper seeks to determine how French philology students eval-uate their intercultural interactive and discursive competence based on their use of address forms in the mother tongue and in the target language. It al-so attempts to establish the impact of students’ knowledge of address forms on classroom interaction and the effectiveness of educational dis-course. The analysis of the data, collected by means of a survey, made it possible to identify prototypical address forms in Polish and French, estab-lish their functions and reveal situations in which they have real relevance.